جودة الحياة الوظيفية لدى أساتذة كلية العلوم الاجتماعية والإنسانية - حمامة, عمار; الشايب, محمد الساسي (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة الحالية للتعرف على مدى تأثير بعض المتغيرات الديمغرافية على جودة الحياة الوظيفية لدى أساتذة كلية العلوم الاجتماعية والإنسانية بجامعة الشهيد "حمه لخضر" بمدينة الوادي.لتحقيق أهداف الدراسة استخدم الباحث المنهج الوصفي التحليلي وقد تكون مجتمع الدراسة من أساتذة جامعة الشهيد "حمه لخضر", والبالغ عددهم 776 أستاذا. وقد استخدم الباحث أداة الاستبيان الذي أعده لجمع البيانات، وبعد التأكد من صدق الأداة وثباتها تم تطبيقها على عينة الدراسة. وقد تم استرجاع (88) استبيان من أصل (115). وقد توصلت الدراسة إلى النتائج التالية: - عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات تقدير أفراد العينة لمستوى جودة الحياة الوظيفية تعزى لمتغيرات الجنس والرتبة الأكاديمية. - وجود فروق ذات دلالة إحصائية بين متوسطات درجات تقدير أفراد العينة لمستوى جودة الحياة الوظيفية تعزى لمتغير عدد سنوات الخدمة. The present study aimed to identify the effect of some demographic variables on the quality of work life among the university professors of the Faculty of Social and Human Sciences at El-Oued University. In order to achieve the study objectives, the researcher used descriptive analytical method, and the study society consisted of the professors of the faculty of social and human sciences in the El-Oued University, their number was 115 professors. The researcher developed a questionnaire as a tool for collecting data consisting of (54) items distributed on the following dimensions: organizational aspects, physical and moral working environment and financial aspects. After verifying its validity reliability; the questionnaire was administered to the study sample. A total of 88 questionnaires were retrieved out of 115. The study concluded the following results: - There were no statistically significant differences between the average scores of the sample members' appreciation for the level of quality of work life due to gender and academic rank variables. - There were statistically significant differences between the average scores of the sample members' appreciation for the level of quality of work life due to years of service variable.
بجامعة الشهيد "حمه لخضر" بالوادي في ظل بعض المتغيرات الديمغرافية
مقال
Keywords: جودة الحياة الوظيفية؛ المتغيرات الديمغرافية؛ الأستاذ الجامعي; quality of work life - demographic variables - university professo